O (Des)velamento do cotidiano do indivíduo soropositivo: convivências e resistências - Vieira, Neiva Francenely Cunha (Brazilian Journal of Sexually Transmitted Diseases, 1997)
The last decade che public health system world-wide have been challenged tocontrol che fase spread of the human immunedeficiency cuquired syndrome (AIDS) since the epidemie have started in the 1980. Many researches have been developing in chis field from de experimental to social realm study due to the range of che biological and social issues that it has raised since chen. This research aims to draw attention to the psychosocials reactions of the HIV-positive patientes in their daily social relarionships. lt wants to show the need to uncover their perceptions, feelings and how those experiences have affected their process of care. The research participants were male and female HIV-positive patients from an ambulatory service of the governmenc hospital. For data collection, we conducted interviews, participant observation and life history. Data allowed us to a deep comprheension and interpretation of HIVpositive patients’ difficulties on the course of their social relationships. We advocated that those feelings and experiences must be considered in the process of caring and the whole assintance of this patients’ needs.